Nilai-Nilai Budaya dalam Novel 9 Summers 10 Autumns Karya Iwan Setyawan dan Implikasi terhadap Pembelajaran Bahasa - Pryska Anggrainy B (Universitas Negeri Padang, 2022)
The purpose of this research is as follows. First, describe the cultural value contained in the novel9 Summers 10 Autumns by Iwan Setyawan. Second, describe the implications for language learning. This type of research is qualitative research using descriptive methods. The data in this study are words, phrases, and sentences in the novel 9 Summers 10 Autumns by Iwan Setyawan which relates to cultural values that are traced based on the speech or actions of figures that can be formulated as cultural value data. The data source in this study is the novel 9 Summers 10 Autumns by Iwan Setyawan published by publisher Gramedia in Jakarta in July 2013 which consists of 221 pages. The novel already has an ISBN and Copyright Act. As for the basis in establishing the object of research is the part that contains the cultural value of human relations with God, the cultural value of human relations with oneself, and the cultural value of human relations with others. Instruments in this research, namely library studies and record techniques. Data analysis is done, namely describing, classifying, analyzing data, and compiling reports. The results of this study are as follows. First, the cultural values in the novel 9 Summers 10 Autumns by Iwan Setyawan found three types of cultural values that each have several parts. The three types of cultural values are the cultural value of man's relationship with God, the cultural value of human relations with oneself, and the cultural value of human relations with others. Second, the cultural values in the novel 9 Summers 10 Autumns by Iwan Setyawan can be implications for language learning, namely the text of the high school class XII novel.